2018
DOI: 10.1038/d41586-018-02108-9
|View full text |Cite
|
Sign up to set email alerts
|

How to make replication the norm

Abstract: position-it is too crude a guide to contribution p.423 EARTH OBSERVATION History shapes where, when, why and how we collect data p.423 BIOLOGY From fly room to fly boom: how labs filled up with Drosophila p.421 SOCIETY Is Steven Pinker too optimistic about our troubled times? p.420 How to make replication the norm The publishing system builds in resistance to replication. Paul Gertler, Sebastian Galiani and Mauricio Romero surveyed economics journals to find out how to fix it. Efforts to replicate research stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 8 publications
0
42
0
1
Order By: Relevance
“…Despite these advantages, publishing results in a reproducible way is still not common practice (Reichman et al 2011), which is part of the reason why some have proclaimed a 'reproducibility crisis' (Baker 2016). A recent study in economics (Gertler et al 2018) has shown that even when authors make the data and code publicly accessible, it is not guaranteed that readers can successfully reproduce the results published in the paper. On top of that, the inconsistent usage of the terms reproducibility and replicability within and across disciplines can cause further CONTACT Markus Konkol m.konkol@uni-muenster.de Supplemental data for this article can be accessed here.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, publishing results in a reproducible way is still not common practice (Reichman et al 2011), which is part of the reason why some have proclaimed a 'reproducibility crisis' (Baker 2016). A recent study in economics (Gertler et al 2018) has shown that even when authors make the data and code publicly accessible, it is not guaranteed that readers can successfully reproduce the results published in the paper. On top of that, the inconsistent usage of the terms reproducibility and replicability within and across disciplines can cause further CONTACT Markus Konkol m.konkol@uni-muenster.de Supplemental data for this article can be accessed here.…”
Section: Introductionmentioning
confidence: 99%
“…Second, even if the data and code are available, independent researchers are often not able to reproduce the results. These two patterns have been empirically established in the social sciences (Dewald et al, 1986;McCullough et al, 2006;Wicherts et al, 2006;In'nami and Koizumi, 2010;Wicherts et al, 2011;Vanpaemel et al, 2015;Wicherts and Crompvoets, 2017;Gertler et al, 2018;Chang and Li, 2018;Stockemer et al, 2018;Wood et al, 2018), as well as other scientific fields (Savage and Vickers, 2009;Ioannidis et al, 2009;Vandewalle et al, 2009;Gilbert et al, 2012;Ostermann and Granell, 2017;Collberg and Proebsting, 2016;Andrew et al, 2015;Stodden et al, 2018;Konkol et al, 2019;Hardwicke and Ioannidis, 2018;Alsheikh-Ali et al, 2011;Vines et al, 2014;Rowhani-Farid and Barnett, 2016;Naudet et al, 2018;Campbell et al, 2019). Although the magnitude of the problem differs by field and across time, the limited availability of replication materials and the limited usefulness of the materials that are available are consistent patterns.…”
Section: Introductionmentioning
confidence: 94%
“…Brown and Wood note that the replication program at 3ie first selects candidate studies for replication, then matches researchers to do the replication. Nevertheless, this suspicion is difficult to shake given the predilection of journals to publish replications that overturn the results of an original study, thus incentivizing replication authors to find faults (Gertler, Galiani, and Romero, 2018). This motivates the last takeaway.…”
Section: Takeawaysmentioning
confidence: 99%